A method for evaluating the effect of dissolved organic matter on the photoaging behavior of microplastics

By measuring various indicators of dissolved organic matter and microplastics, combining adsorption models and free radical detection, the photoaging behavior of microplastics is analyzed, and the problem of lack of systematic evaluation methods in the existing technology is solved, and a comprehensive assessment of the photoaging behavior of microplastics and effective assessment of ecological risks is achieved.

CN115656017BActive Publication Date: 2025-04-29GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211297378.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-21
Publication Date
2025-04-29
Estimated Expiration
2042-10-21

AI Technical Summary

Technical Problem

The lack of systematic and comprehensive evaluation methods in the prior art to study the impact of dissolved organic matter from different sources on the photoaging behavior of microplastics, resulting in insufficient assessment of the migration and transformation laws and ecological risks of microplastics in water environments.

Method used

By determining the aromaticity, component conditions and relative abundance of dissolved organic matter, as well as the particle size, surface morphology, crystallinity and carbonyl index of microplastics, combined with adsorption model and free radical detection, the photoaging behavior of microplastics was analyzed.

Benefits of technology

It provides an accurate, comprehensive and systematic microplastic photoaging assessment system that can reflect microplastic photoaging behavior and provide important guidance for its ecological risk assessment in water environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115656017B_ABST
    Figure CN115656017B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of environmental technology, and specifically relates to an evaluation method for the effect of dissolved organic matter on the photoaging behavior of microplastics. The method provides a comprehensive and systematic evaluation system for the photoaging of microplastics, that is, the photoaging behavior of microplastics is reflected by measuring indicators such as the apparent morphology, particle size, crystallinity, and carbonyl index, and the aromaticity, three-dimensional fluorescence, and component changes of dissolved organic matter from different sources during the photoaging process are combined with the detection of free radicals to analyze the photoaging behavior of microplastics, providing important guidance for the evaluation of the photoaging behavior of microplastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of environmental technology and more specifically relates to a method for evaluating the effect of dissolved organic matter on the photoaging behavior of microplastics. Background Art

[0002] Microplastics, as a new type of organic pollutant, are widely distributed in the aquatic environment and migrate and transform under the influence of external forces (such as wind, rivers and ocean currents). Due to their small particle size and large specific surface area, they easily adsorb persistent organic pollutants and heavy metals in the environment, accelerate water pollution, and threaten the ecological environment and even human health. Studies have shown that microplastics can enter the human body through the food chain, induce tissue inflammation, and even damage immune cells. Therefore, explaining the migration and transformation of microplastics in the aquatic environment is of great significance for assessing the impact on the aquatic ecological environment.

[0003] The migration and transformation of microplastics are affected by a variety of environmental factors, which change their environmental behavior. Among them, the photoaging of microplastics in the environment is an important prerequisite for studying their migration and transformation in the aquatic environment, which is affected by different environmental factors such as pH, dissolved organic matter (DOM), ion concentration, etc. Among them, DOM, as one of the more photochemically active substances in nature, can mediate the generation of a variety of free radicals, thereby affecting the migration, transformation and spatial distribution of environmental pollutants (see: Science Bulletin, 2021, 66(36): 4619-4632). Therefore, the interaction between DOM and microplastics is an important part of the study of microplastic photoaging that cannot be ignored.

[0004] DOM is a complex organic matter composed of functional groups such as amino acids, aliphatics and aromatics containing nitrogen, phosphorus and sulfur, and is ubiquitous in the environment. DOM from different sources has different components and different photochemical activities, which affect the photochemical behavior of pollutants in the environment (such as polycyclic aromatic hydrocarbons). However, in current research, the mechanism of action of DOM from different sources on the photoaging of microplastics is still unclear. On the one hand, DOM contains a large number of conjugated chromophores that may compete for photon absorption during the photoaging of microplastics, resulting in a light shielding effect, thereby inhibiting the photoaging of microplastics. On the other hand, DOM will be excited to form a triplet state ( 3 DOM * ), or react with oxygen-containing species (such as water, oxygen) to form reactive oxygen species (ROS), such as hydroxyl radicals (·OH), singlet oxygen ( 1O2), etc., thereby accelerating the photoaging of microplastics. The differences in the main components of DOM from different sources determine that their ability to produce ROS is also different. The content of aromatic components and oxygen-containing functional groups in DOM is the main factor affecting the generation of ROS. It can be seen that studying the mechanism of action of DOM from different sources on the photoaging of microplastics is of great significance for explaining the migration and transformation laws of microplastics in aquatic environments, as well as evaluating the ecological risks of microplastics in aquatic environments. However, a large number of studies have focused on the adsorption and enrichment of environmental substances by microplastics, and there is no systematic and comprehensive evaluation method to explain the photoaging behavior of microplastics under the influence of DOM. Therefore, it is urgent to develop an evaluation method for the effect of DOM from different sources on the photoaging behavior of microplastics in aquatic environments. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defects and shortcomings in the existing microplastic photoaging research system and provide an evaluation method for the effect of soluble organic matter on the photoaging behavior of microplastics.

[0006] Another object of the present invention is to provide the application of the evaluation method in evaluating the photoaging behavior of microplastics.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] A method for evaluating the effect of dissolved organic matter on the photoaging behavior of microplastics comprises the following steps:

[0009] S1. Determine the aroma, composition and relative abundance of dissolved organic matter;

[0010] S2. Determine the particle size, surface morphology, crystallinity and carbonyl index of microplastics to reflect the photoaging behavior of microplastics;

[0011] S3. Determine the adsorption model to reflect the adsorption behavior of microplastics on dissolved organic matter:

[0012] Pseudo-first-order kinetic model: Ln(q t -q e )=Lnq e -k1t

[0013] Pseudo-second-order kinetic model:

[0014] Where: q e is the theoretical adsorption amount of dissolved organic matter on microplastics when adsorption equilibrium is reached, q t is the amount of dissolved organic matter adsorbed on microplastics at a certain adsorption time t, and the unit is mg / g; k1 represents the first-order kinetic adsorption rate, and the unit is min -1 ; k2 represents the secondary kinetic adsorption rate, in g / (mg min-1 );

[0015] S4. Determine the main free radicals that affect microplastics caused by dissolved organic matter, use the particle size reduction rate of microplastics to represent the free radical activity, and analyze the photoaging behavior of microplastics.

[0016] Furthermore, the calculation formula of the aromaticity is as follows:

[0017]

[0018] Where: SUVA 254 Refers to the aroma of the test sample; UV 254 It is the absorbance of the test sample at 254nm; DOC is the concentration of dissolved organic carbon in the test sample, and the unit is mg C / L.

[0019] Furthermore, the crystallinity is calculated by performing an X-ray diffraction (XRD) test on the microplastics, and the calculation formula is as follows:

[0020]

[0021] Where: Crystallinity is the crystallinity of microplastics; I c is the crystallization peak area; I a is the non-crystalline peak area.

[0022] Furthermore, the carbonyl index is calculated by Fourier transform infrared spectroscopy (FTIR) testing of microplastics, and the calculation formula is as follows:

[0023]

[0024] Where: CI is the carbonyl index; A C=O The Fourier transform infrared spectrum shows the C=O position (1750cm -1 The absorption peak area of ​​​​A reference is the reference absorption peak area.

[0025] Furthermore, the reference absorption peak in the FTIR graph is determined by the type of microplastics.

[0026] Preferably, the reference absorption peak in the FTIR graph is selected as a wavelength of 1450 cm according to PLA microplastics. -1 The CH stretching vibration peak.

[0027] Furthermore, the calculation formula of the particle size reduction rate is as follows:

[0028]

[0029] Where: SR is the particle size reduction rate; St is the particle size of the microplastics at time t of illumination, in μm; S0 is the initial particle size of the microplastics, in μm.

[0030] Preferably, the concentration of the dissolved organic matter is 6 to 12 mg C / L.

[0031] Preferably, the microplastic is any one of polystyrene microplastic, polyethylene microplastic and polylactic acid (PLA) microplastic.

[0032] More preferably, the microplastic is polylactic acid microplastic.

[0033] In addition, the present invention also provides the application of the evaluation method in evaluating the photoaging behavior of microplastics.

[0034] Furthermore, the photoaging behavior of microplastics is the photoaging behavior of microplastics in a water environment.

[0035] The present invention has the following beneficial effects:

[0036] The present invention provides an accurate, comprehensive and systematic evaluation system for the photoaging of microplastics, which reflects the photoaging behavior of microplastics by measuring indicators such as apparent morphology, particle size, crystallinity, carbonyl index, etc., combined with the measurement of the aromaticity of soluble organic matter from different sources, three-dimensional fluorescence and component changes during the photoaging process, and further analyzes the photoaging behavior of microplastics through the detection of free radicals, providing important guiding significance for the evaluation of the photoaging behavior of microplastics. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The three-dimensional fluorescence (a-b), aroma (c), and relative abundance diagrams of components (d-h) of NDOM and BDOM measured in Example 3 of the present invention (I: tyrosine-like protein component; II: tryptophan-like protein component; III: fulvic acid-like component; IV: soluble microbial metabolic byproduct component; V: humic acid-like component);

[0038] Figure 2 This is a graph of particle size change-time of PLA microplastics subjected to light aging under the action of NDOM and BDOM as measured in Example 4 of the present invention;

[0039] Figure 3 The scanning electron micrographs of the initial (a) PLA microplastics measured in Example 4 of the present invention and after 7 days of light aging under the action of NDOM (b) and BDOM (c);

[0040] Figure 4 This is a crystallinity-time diagram of PLA microplastics subjected to light aging under the action of NDOM and BDOM as measured in Example 4 of the present invention;

[0041] Figure 5 This is a carbonyl index-time graph of photoaging of PLA microplastics under the action of NDOM and BDOM measured in Example 4 of the present invention;

[0042] Figure 6 This is a diagram of the aroma-time of NDOM and BDOM during the photoaging process of PLA microplastics measured in Example 4 of the present invention;

[0043] Figure 7 The relative abundance-time diagram of NDOM (a) and BDOM (b) components during the photoaging process of PLA microplastics measured in Example 4 of the present invention;

[0044] Figure 8 The adsorption curves and adsorption kinetics simulations of PLA microplastics on NDOM and BDOM measured in Example 5 of the present invention;

[0045] Fig. 9 This is a Fourier transform infrared spectrum of PLA microplastics after adsorption of NDOM and BDOM for 3 days measured in Example 5 of the present invention;

[0046] Fig.10 This is a graph showing the particle size changes of PLA microplastics that undergo photoaging under the action of NDOM and BDOM before and after the active oxygen species quenching experiment in Example 6 of the present invention. DETAILED DESCRIPTION

[0047] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0048] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0049] Example 1 Preparation of dissolved organic matter

[0050] Take 50g corn stalks, wash and dry them to constant weight, crush and sieve to get stalk powder, then put the stalk powder into a muffle furnace, carbonize it at 450℃ for 2h, and heat it up at a rate of 5℃ / min. Take it out after cooling it to room temperature to get corn stalk biomass charcoal. Weigh 2g of the obtained biochar in 20mL deionized water, so that the solid-liquid ratio is 1:10, ultrasonicate for 15min, then oscillate at 120rpm in the dark for 72h, and finally centrifuge at 1000rpm and filter through a 0.45um filter membrane. Collect the filtrate and store it in a 4℃ refrigerator, named BDOM, and its concentration is measured by a total organic carbon analyzer (TOC) and adjusted to 10mg C / L for standby use.

[0051] Example 2 Preparation of dissolved organic matter

[0052] Weigh 10 mg of Suwannee River Fulvic Acid purchased on the IHSS official website, mix it with 100 mL of deionized water to make the solid-liquid ratio 1:10, then filter it with a 0.45 um filter membrane, collect the filtrate and store it in a refrigerator at 4°C, named NDOM. Its concentration is determined by TOC and adjusted to 10 mg C / L for later use.

[0053] Example 3 Characterization of dissolved organic matter from different sources

[0054] 1. Experimental purpose

[0055] Determine the initial composition of DOM from different sources.

[0056] 2. Experimental methods

[0057] (1) Aroma (SUVA 254 ) determination

[0058] SUVA 254 It is an important indicator used to reflect the content of aromatic compounds. It is the ratio of the absorbance of DOM at 254nm to dissolved organic carbon (DOC). The wavelength range of the UV-visible spectrophotometer is set to 200-700nm. The calculation formula is as follows:

[0059]

[0060] Where: SUVA 254 Refers to the aroma of the test sample; UV 254 It is the absorbance of dissolved organic matter at 254nm, and DOC is the concentration of dissolved organic carbon in dissolved organic matter, which is measured by total organic carbon analyzer TOC.

[0061] (2) Components and relative abundance determination

[0062] The three-dimensional fluorescence spectrum can effectively identify the fluorescent components in DOM. It is measured by a fluorescence spectrophotometer. The excitation wavelength (Ex) scan range is 200-500nm, the emission wavelength (Em) scan range is 250-550nm, the scanning interval is 50nm, the slit width is 5nm, and the scanning speed is 12000nm / min. The three-dimensional fluorescence spectrum of the component distribution is obtained. Based on the fluorescence regional integration technology, the three-dimensional fluorescence spectrum can be divided into five regions (I~V). Regions I and II (Ex<250nm, Em<380nm) are tyrosine-like protein components and tryptophan-like protein components, respectively; region III (Ex<250nm, Em>380nm) is fulvic acid-like; region IV (Ex>250nm, Em<380nm) is soluble microbial metabolic byproducts; region V (Ex>250nm, Em>380nm) is humic acid-like.

[0063] 3. Experimental results

[0064] Figure 1 The three-dimensional fluorescence (a-b), aroma (c), and relative abundance diagrams (d-h) of the NDOM prepared in Example 1 and the BDOM prepared in Example 2 of the present invention, wherein region IV is respectively tyrosine-like protein component, tryptophan-like protein component, fulvic acid-like component, soluble microbial metabolic byproduct component, and humic acid-like component. Figure 1 The Roman numerals in d~h represent the components corresponding to Figure 1 a or Figure 1 The Roman numerals in b represent the components. As can be seen from the figure, humic acid-like substances are the main components in both NDOM and BDOM, and the content of humic acid-like substances in NDOM is higher than that in BDOM, while the contents of the other four components are lower than those in BDOM. Figure 1 The aroma of NDOM in c was significantly higher than that of BDOM, indicating that the initial NDOM contained more aromatic components.

[0065] Example 4 Experiment on photoaging of microplastics by DOM from different sources

[0066] 1. Experimental purpose

[0067] Exploring the photoaging effect of DOM on microplastics

[0068] 2. Experimental methods

[0069] At 25°C, 30 mg PLA microplastics (particle size of about 100 um) were added to 30 mL NDOM or BDOM solution (dissolved organic carbon content of 10 mg C / L) and mixed, ultrasonicated for 15 min, placed in a multi-channel photoreactor under illumination (selected 365 nm illumination wavelength) for 7 days, and sampled every other day. The particle size, surface morphology, crystallinity and carbonyl index of microplastics were tested by inverted fluorescence microscopy, SEM, XRD, FTIR and respectively to reflect the photoaging behavior of microplastics. NDOM and BDOM were tested by UV-visible spectrophotometer and fluorescence spectrophotometer to reflect the changes in aromaticity and components of DOM from different sources during the reaction. The illumination wavelength selected in the reaction was 365 nm. Three parallel groups were set up for each experiment. The blank control (Pure water-PLA) replaced DOM with pure water, and the dark control (PLA in dark) remained unchanged except for the absence of light.

[0070] (1) Particle size measurement

[0071] The microplastics were first filtered and separated, and the particle size of the microplastics before and after the action of dissolved organic matter was observed using an inverted fluorescence microscope. 50 representative samples were selected for measurement, and the average particle size was calculated.

[0072] (2) Surface morphology measurement

[0073] Scanning electron microscopy was used to observe the morphology of microplastics before and after the action of dissolved organic matter.

[0074] (3) Determination of crystallinity

[0075] The crystallinity of microplastics was determined by XRD; the target material in XRD was a copper target, the scanning range was 5-90°, and the scanning speed was 10° / min; the calculation formula was as follows:

[0076]

[0077] Where: I c is the crystallization peak area; I a is the non-crystalline peak area.

[0078] (4) Carbonyl index determination

[0079] The carbonyl index (CI) of microplastics was determined by FTIR. The scanning range was 4000-400 cm -1 , resolution 4cm -1 , the calculation formula is as follows:

[0080]

[0081] Where: AC=O The Fourier transform infrared spectrum shows the C=O position (1750cm -1 The absorption peak area of ​​A reference is the reference absorption peak area. Among them, the reference absorption peak of polylactic acid (PLA) microplastics is 1450cm -1 The CH stretching vibration peak.

[0082] (5) Aroma Determination

[0083] Test method reference example 3

[0084] (6) Determination of relative abundance of components

[0085] Test method reference example 3

[0086] 3. Experimental results

[0087] (1) Particle size measurement results

[0088] Figure 2 The particle size change-time diagram of the PLA microplastics under the action of NDOM and BDOM during photoaging of the present invention. Taking the particle size as an indicator of the degree of photoaging of PLA microplastics, after 3 days of light exposure, compared with the direct photoaging of PLA microplastics (30.4%), the particle size of PLA microplastics under the action of NDOM and BDOM decreased by 62.8% and 59.1%, respectively. Among them, the photoaging rate of PLA microplastics under the action of NDOM (9.7) is greater than that of BDOM (7.2), and both are higher than the direct photoaging rate of PLA microplastics (5.1), indicating that NDOM and BDOM both promote the photoaging of PLA microplastics to varying degrees, and the promotion effect of NDOM is more obvious.

[0089] Among them, the photoaging rate is obtained by fitting the data of PLA particle size decrease, and derivatizing the inflection point on the fitting curve while keeping the horizontal axis at the same value, that is, making a tangent at the inflection point. The absolute value of the tangent slope represents the particle size decrease rate, and the obtained particle size decrease rate represents the photoaging rate.

[0090] (2) Morphology measurement results

[0091] Figure 3 The scanning electron microscope images of the initial (a) PLA microplastics and the photo-aging under the action of NDOM (b) and BDOM (c) described in the present invention. The surface of the original PLA microplastics is smooth and has no holes, but after 7 days of light exposure in NDOM or BDOM solution, the surface becomes rough and a large number of pores appear, indicating that NDOM and BDOM promote the photo-aging and surface damage of PLA microplastics. After the action of NDOM, the surface of PLA microplastics has more pores, indicating that its effect is more significant.

[0092] (3) Crystallinity measurement results

[0093] Figure 4 The crystallinity-time diagram of PLA microplastics under light aging under NDOM and BDOM of the present invention. The crystallinity increases with the increase of illumination time. After 7 days of illumination, the crystallinity of PLA microplastics aged under NDOM and BDOM is 2.5% and 1.2% higher than that under direct photolysis, respectively, indicating that both NDOM and BDOM promote the changes in the structure and crystal form of PLA microplastics, and NDOM has a better promoting effect.

[0094] (4) Carbonyl index results

[0095] Figure 5 The carbonyl index-time diagram of the PLA microplastics photo-aged under the action of NDOM and BDOM described in the present invention. The carbonyl index of the PLA microplastics under direct photolysis, NDOM or BDOM all tended to be stable after 3 days. At the same time, the carbonyl index under the action of NDOM and BDOM was relatively close, about 1.2 times that under direct photolysis, indicating that more oxygen-containing functional groups were generated on the surface of the PLA microplastics after photo-aging under the action of NDOM and BDOM.

[0096] (5) Aroma measurement results

[0097] Figure 6 This is a time diagram of the aroma of NDOM and BDOM during the photoaging process of PLA microplastics described in the present invention. The aroma of NDOM and BDOM first decreases with the increase of illumination time, reaching a minimum value on the third day, and the aroma of NDOM is significantly lower than that of BDOM after the reaction, indicating that the aromatic components in DOM are partially converted during the photoaging process and may affect the photoaging process of microplastics, among which the aromatic components of NDOM are converted more thoroughly.

[0098] (6) Results of relative abundance determination of components

[0099] Figure 7 The relative abundance-time diagram of the components of NDOM (a) and BDOM (b) during the photoaging process of PLA microplastics described in the present invention. The Roman numerals in the figure represent the components corresponding to Figure 1 a or Figure 1 The Roman numerals in b represent the components. The content of humic acid-like components in NDOM and BDOM decreased with the increase of light exposure time. By the 7th day, they decreased by 64.3% and 42.5%, respectively. Humic acid-like components contain a large number of aromatic components, indicating that the aromatic components in DOM are transformed during the photoaging process and may affect the photoaging process of microplastics. Among them, the aromatic components of NDOM are transformed more thoroughly.

[0100] Example 5 Adsorption experiment of DOM from different sources and microplastics

[0101] 1. Purpose of the experiment

[0102] Further confirming the interaction between DOM and microplastics

[0103] 2. Experimental methods

[0104] In the dark, 30 mg PLA microplastics (particle size of about 100 μm) were added to 30 mL NDOM or BDOM solution (dissolved organic carbon content of 10 mg C / L) and mixed, ultrasonicated for 15 min, placed in a constant temperature incubator at 120 rpm for 72 h, and samples were taken at 0, 2, 4, 6, 8, 12, 24, 36, 48, and 72 h. Quantitative test analysis was performed by TOC and FTIR.

[0105] The equilibrium equations of pseudo-first-order kinetics and pseudo-second-order kinetics models are as follows:

[0106] Pseudo-first-order kinetic model: Ln(q t -q e )=Lnq e -k1t

[0107] Pseudo-second-order kinetic model:

[0108] Where: q e (mg / g) is the theoretical adsorption amount of dissolved organic matter on microplastics when adsorption equilibrium is reached, q t (mg / g) is the amount of dissolved organic matter adsorbed on microplastics at a certain adsorption time t; k1 represents the first-order kinetic adsorption rate, in min -1 ; k2 represents the secondary kinetic adsorption rate, in g / (mg min -1 ).

[0109] FTIR tests the components adsorbed by microplastics. The specific steps are as follows: the adsorbed microplastics are separated and dried in a cold dryer for 24 hours, followed by FTIR testing with a scanning range of 4000-400 cm -1 , resolution 4cm -1 .

[0110] 3. Experimental results

[0111] (1) Adsorption model results

[0112] Figure 8The adsorption curves and adsorption kinetics simulations of PLA microplastics on NDOM and BDOM are shown in Table 1. The adsorption data of PLA microplastics on NDOM and BDOM are more consistent with the adsorption pseudo-second-order kinetics simulation. At the same time, the secondary kinetics adsorption rate of PLA microplastics on NDOM (0.28) is higher than that of BDOM (1.58×10 -3 ), indicating that the adsorption process of PLA microplastics with NDOM and BDOM is mainly controlled by chemical adsorption, and the adsorption affinity for NDOM is stronger.

[0113] Table 1 Kinetic parameters of NDOM and BDOM adsorption on PLA microplastics

[0114]

[0115] Note: e .exp is the actual adsorption amount obtained from the experiment, q e It is the theoretical adsorption amount calculated after fitting different kinetics.

[0116] (2) Fourier transform infrared spectroscopy results

[0117] Fig. 9 This is the Fourier infrared spectrum of the PLA microplastics of the present invention after adsorption of NDOM and BDOM for 3 days. NDOM and BDOM are located at 2846 cm -1 (aliphatic CH) and 2922cm -1 The peak intensity at (aliphatic CH2) increased, indicating that PLA microplastics mainly adsorbed aliphatic components of NDOM and BDOM, resulting in the enrichment of aromatic components in the solution, which were converted into free radicals during photolysis to promote the aging of microplastics.

[0118] Example 6 Free radical quenching experiment during photoaging of microplastics under the action of DOM from different sources

[0119] 1. Purpose of the experiment

[0120] Detection of major free radicals

[0121] 2. Experimental methods

[0122] At 25°C, 30 mg PLA microplastics (particle size of about 100 μm) were added to 30 mL NDOM or BDOM solution (dissolved organic carbon content of 10 mg C / L), and 10 mM isopropanol (IPA, used to quench ·OH free radicals) and isoprene (Isoprene, used to quench 3 DOM * free radicals) and L-histidine (L-histidine, used to quench1 O2 free radical) free radical quencher, the resulting mixed solution was ultrasonicated for 15 minutes, then placed in a multi-channel photoreactor under illumination ((selected 365nm illumination wavelength) for 3 days, and then the microplastic particle size was tested and analyzed using an inverted fluorescence microscope. Among them, the quencher concentration was 10mM, and 3 parallel groups were set up for each experiment. The control group replaced the quencher with water. The particle size reduction rate (SR%) represents the free radical activity, and the calculation formula is as follows:

[0123]

[0124] In the formula: St is the particle size of microplastics at time t of illumination, and S0 is the initial particle size of microplastics.

[0125] 3. Experimental results

[0126] Fig.10 The figure is a graph showing the particle size change of PLA microplastics under the action of NDOM and BDOM before and after the quenching experiment described in the present invention. After quenching OH, the particle size reduction rate of PLA microplastics under the action of NDOM decreased from 62.8% to 9.1%, and the particle size reduction rate of PLA microplastics under the action of BDOM decreased from 59.1% to 17%, while the quenching 1 After O2, the particle size reduction rates of PLA microplastics under the action of NDOM and BDOM were 28.1% and 27.8%, respectively. 3 DOM * After NDOM and BDOM, the particle size reduction rate of PLA microplastics was still as high as 30.9% and 33.9%, respectively, which indicates that ·OH, 1 O2 and 3 DOM * They are all free radicals in the photoaging process of microplastics caused by DOM from different sources, and ·OH is the main free radical in the photoaging process.

[0127] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for evaluating the effect of dissolved organic matter on the photoaging behavior of microplastics, characterized in that: The following steps are involved: S1. Determine the aroma, composition and relative abundance of dissolved organic matter; S2. Determine the particle size, surface morphology, crystallinity and carbonyl index of microplastics to reflect the photoaging behavior of microplastics; S3. Determine the adsorption model to reflect the adsorption behavior of microplastics on dissolved organic matter: Pseudo-first-order kinetic model: Pseudo-second-order kinetic model: Where: q e is the theoretical adsorption amount of dissolved organic matter on microplastics when adsorption equilibrium is reached, q t is the amount of dissolved organic matter adsorbed on microplastics at a certain adsorption time t, and the unit is mg / g; k1 represents the first-order kinetic adsorption rate, and the unit is min -1 ; k2 represents the secondary kinetic adsorption rate, the unit is g / (mg‧min -1 ); S4. Determine the main free radicals of dissolved organic matter acting on microplastics, use the particle size reduction rate of microplastics to represent the free radical activity, and analyze the photoaging behavior of microplastics; The carbonyl index is calculated by Fourier transform infrared spectroscopy testing of microplastics, and the calculation formula is as follows: Where: CI is the carbonyl index; A C=O is the absorption peak area at C=O in the Fourier transform infrared spectrum; A reference is the reference absorption peak area; The reference absorption peak is determined by the type of microplastics; The microplastic is any one of polystyrene microplastic, polyethylene microplastic and polylactic acid microplastic.

2. The evaluation method according to claim 1, characterized in that: The calculation formula of the aromaticity is as follows: Where: SUVA 254 Refers to the aroma of the test sample; UV 254 is the absorbance of the test sample at 254 nm, and DOC is the concentration of dissolved organic carbon in the test sample, expressed in mg C / L.

3. The evaluation method according to claim 1, characterized in that: The crystallinity is calculated by performing an X-ray diffraction test on the microplastics, and the calculation formula is as follows: Where: Crystallinity is the crystallinity of microplastics; I c is the crystallization peak area; I a is the non-crystalline peak area.

4. The evaluation method according to claim 1, characterized in that: The calculation formula of the particle size reduction rate is as follows: Where: SR is the particle size reduction rate; S t is the particle size of microplastics at time t of illumination, in μm; S0 is the initial particle size of microplastics, in μm.

5. The evaluation method according to claim 1, characterized in that: The concentration of dissolved organic matter is 6~12 mgC / L.

6. Application of any of the evaluation methods described in claims 1 to 5 in evaluating the photoaging behavior of microplastics.

7. The use according to claim 6, characterized in that: The photoaging behavior of microplastics is the photoaging behavior of microplastics in a water environment.

Citation Information

Patent Citations

  • Micro-plastic aging behavior evaluation method

    CN114563370A

  • Method and apparatus for measuring concentration of dissolved organic carbon in water

    WO2022148252A1